Pembelajaran Akidah Akhlak melalui Pendekatan Konstruktivisme untuk Mencegah Radikalisasi (Survei terhadap Pembelajaran General and Character Education di STIT Alquraniyah Manna Bengkulu Selatan) - Boby Hendro Wardono; Wiwid Suryono; Sophia Rahmi; Nur Azizah; Aat Ruchiat Nugraha; Rian Novita (Journal on Education, 2024)
This research aims to evaluate the effectiveness of learning moral beliefs using a constructivist approach in preventing radicalization in the Islamic education environment, especially at STT Alquraniyah Manna South Bengkulu. The research method used was a survey of students who took part in General and Character Education learning with a constructivist approach. The research results show that learning with a constructivist approach is successful in increasing students' understanding, critical, analytical, and tolerance and humanity values, thus helping to prevent radicalism. The implication of this research is the importance of implementing responsive and interactive learning methods in forming an attitude of moderation and maintaining harmony in society. This research makes an important contribution in the context of preventing radicalization through a holistic and proactive educational approach.